Intersections of Gender/Sex, Multiculturalism and Religion: Young Muslim Minority Women in Contemporary Bali. Issue 3 (3rd July 2017) - Parker, Lyn
Abstract: This article examines the experience of Muslim female students in high schools in Bali. Since the religion of the majority of the population of Bali is Balinese Hinduism, these young women are part of a Muslim minority – unusual in Indonesia. Data were obtained through interviews and ethnographic fieldwork conducted in 2010. Interviewees were mainly Muslim students, but teachers and Muslim parents were also consulted. Some of the students are a minority within a state senior high school, and some attend a private Islamic school in Denpasar. Interviewees identified choice of school and the wearing of the jilbab (Islamic head-scarf) as issues for them in their everyday lives. The Islamic school is (mis-)perceived as a morally safe environment by parents. The state school does not allow the wearing of the jilbab, showing the limits of multiculturalism in Bali. While the jilbab should express piety and morality, there is some hypocrisy among some young jilbab -wearing women. Some young women have internalised the Balinese objection to poor Muslim immigrants, and feel inferior when they wear the jilbab . The data suggest that their female sex/gender flags their unequal Muslim-minority status in ways that Muslim-minority men do not experience.